The Effect of Effleurage Massage Techniques on Afterpains Pain in Multigravida Postpartum Mothers at the Tanjung Selamat Health Center, Kec. Padang Tualang, Kab. Leaving in 2022 - Zuidah (Science Midwifery, 2022)
Afterpains pain in multigravida postpartum women is caused by contractions in continuous relaxation of the uterus. Effleurage is a massage technique that is safe, easy to do, doesn't require a lot of tools, doesn't cost money, doesn't have side effects and can be done alone or with the help of others. The purpose of this study was to determine the effect of the Effleurage Massage Technique on Afterpains Pain in Multigravida Postpartum Mothers at UPT Puskesmas Tanjung Selamat, Kec. Padang Tualang, Kab. Langkat. The design of this research is descriptive with a quasi-experimental study approach. The sampling technique used is purposive sampling, namely the technique of determining the sample with certain considerations as desired by the researcher. Samples on postpartum mothers were taken with a percentage of 25% so that the sample in this study was 30 people. The results of the study prior to the Effleurage Massage Technique the majority experienced moderate pain as many as 20 respondents (67%). Meanwhile, after the Effleurage Massage Technique, the majority experienced a decrease in mild pain as many as 30 respondents (67%). The conclusion of this study is that there is an effect of Effleurage Massage Technique on Afterpains Pain in Multigravida Postpartum Mothers at UPT Puskesmas Tanjung Selamat, Kec. Padang Tualang, Kab. Langkat. The results of the statistical test using the t test showed that the p value (0.000 < (0.05) means Ha is accepted, so there is an effect of the Effleurage Massage Technique on Afterpains Pain in Multigravida Postpartum Mothers at UPT Puskesmas Tanjung Selamat, Padang Tualang District, Langkat Regency